1995
DOI: 10.1161/01.cir.92.11.3212
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Control of Arterial Distensibility Is Impaired in Chronic Heart Failure

Abstract: These data indicate that conduit artery distensibility is increased by acetylcholine and increased blood flow in healthy subjects but not in CHF patients, whereas the effects of adenosine and GTN on distensibility are preserved in CHF patients. This implies that EDRF-mediated increases in distensibility are impaired in CHF patients, thus adding to cardiac work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
169
2
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(185 citation statements)
references
References 25 publications
5
169
2
7
Order By: Relevance
“…endothelial dysfunction, or by promoting smooth muscle cell proliferation. 23,[25][26][27][28] A recent study by Ramsey et al 29 showed that arterial distensibility is controlled by normal endothelium in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…endothelial dysfunction, or by promoting smooth muscle cell proliferation. 23,[25][26][27][28] A recent study by Ramsey et al 29 showed that arterial distensibility is controlled by normal endothelium in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…19 A number of other studies have described a relationship between various indices of arterial stiffness and endothelial dysfunction in selected patient groups. [21][22][23][24][25] However, these studies require invasive procedures and/or highly specialized equipment and operators. Moreover, only a limited number of studies assessed aortic PWV, the current gold-standard measure of large artery stiffness, and wave reflection characteristics.…”
Section: Mceniery Et Al Endothelial Function and Arterial Stiffnessmentioning
confidence: 99%
“…However, direct evidence of a relationship between endothelial function and more definitive measures of arterial stiffness is largely limited to studies in patients with cardiovascular disease and risk factors, [21][22][23][24][25][26] and the relationship between endothelial function and aortic (carotid-femoral) pulse wave velocity (PWV), the current "gold-standard" measure of stiffness, in healthy normotensive individuals, who are free of the potentially confounding influence of cardiovascular disease, has not been well-described. Moreover, as we 27 and others 28 have shown previously, brachial pulse pressure does not always provide an accurate indication of central pulse pressure, and the relationship between endothelial function and central pulse pressure is unclear.…”
mentioning
confidence: 99%
“…The validity of this method has been confirmed in previous studies. 20,21 Briefly, the diameter of the brachial artery was measured from B-mode ultrasound images with a 7.5-MHz linear array transducer (SSH-160A, Toshiba). Flow velocity in the brachial artery was measured with a pulsed Doppler signal at a 70°angle to the vessel, with the range gate (1.5 mm) in the center of the artery.…”
Section: Endothelial Functionmentioning
confidence: 99%